Europa Środkowa: kryzys koncepcji i terminu, resztki nadziei - Pospíšil, Ivo (Postscriptum Polonistyczne, 2020)
The article discusses a concept of Central Europe and its research implications, as seen within their importance to the Slavonic Studies in Brno. An essential element of any discussion about Central Europe (thus East and West) is a cultural dialogue. The author of the article understands such a dialogue as not only a gentle coexistence and peaceful supplementation but also – a creative confrontation of the participating parties. Under deliberations are also: a problem of evaluating some cultures against others, terms that reveal the offputting attitudes and stereotypes used by some researchers when cultures and literatures of Central Europe are written about. The author analyses the tradition of “CentralEuropeanness” and places it within a wide cultural context. The question about a future of this concept as well as the status of homo Europae centralis is also posited.